Proposed business strategy for â€œauraku skin solutionâ€ in order to gain the competitive advantage - Qonitza, Maghfira; Hamsal, Mohammad (The Indonesian Journal of Business Administration, 2016)
Abstract – Auraku Skin Solution is a company engaged in the services sector, especially skin care. This company is a branch company located in Karawang and was founded in 2011. Currently, there are two competitors in Karawang skin care companies that offers all-in-one skin care and become the winner of the competition. It has an impact on Auraku Skin Solution’s revenue decreased in late 2014 - mid 2015. In order to survive in the competition and to increase revenue, Auraku Skin Solution requires a sustainable competitive advantage in doing business. To gain competitive advantage and win the competition, Auraku Skin Solution must adapt to the new business models canvas development and strategies resulting from the TOWS Strategy. The conclusion of this strategy, Auraku Skin Solution must be added advantages in its business and conduct marketing activities to promote their value proposition. Keywords: Business Strategy, Business Canvas, TOWS Strategy, Skin Care Industry.